Is non-mentored initiation of laparoscopic colorectal surgery safe? Single surgeon initial experience with the first 40 cases - Bakula, Branko (Frontiers in Surgery, 2023)
Introduction Although laparoscopic colorectal surgery is now accepted as a standard procedure in treating colorectal cancer, the proportion of laparoscopically operated patients with colorectal cancer is still generally quite low. The aim of this study is to assess feasibility, safety, and outcomes of a non-mentored initiation of laparoscopic colorectal resections by a young surgeon without previous experience in laparoscopic colorectal surgery. Materials and methods We analyzed the characteristics of the first 40 elective cases of laparoscopic colorectal resections performed by a single surgeon during the period between June 2019 and March 2022. All of the operations were performed without the attendance or supervision of an experienced surgeon in laparoscopic colorectal surgery. The patients were divided into three groups (the early, intermediate, and late group). Results The conversion rate, complications rate, and postoperative recovery were similar among groups. The mean overall operative time was 219.5 min (range 130–420 min) and had reduced significantly during the learning curve (p = 0.047). The overall conversion rate was 12.5%. In two cases (5%), the oncological principles were violated (incomplete total mesorectal excision). In three patients (7.5%), intraoperative complications had occurred (small bowel injury, splenic injury, and significant bleeding from the minor peripancreatic artery). Three cases of major postoperative complications (Clavien–Dindo grade III) were recorded, two of which required reoperation (anastomotic bleeding and fascial dehiscence). There was no 90-day mortality reported. The overall mean number of lymph nodes retrieved was 12.45, which did not differ significantly among groups (p = 0.678). The average follow-up was 13.75 months (range 1–31 months). Cancer recurrence was recorded in four patients (10%). Port-site metastasis was not detected in any of the cases. Conclusion A safe and non-mentored initiation of laparoscopic colorectal surgery with an acceptable rate of complications and acceptable oncological results can be achieved. Still, when compared with a structured initiation in a controlled environment with the supervision of an experienced surgeon in laparoscopic colorectal surgery, the results of a non-mentored initiation are worse in most of the fields, including operative time, conversion rate, complications rate, and duration of hospital stay. Therefore, I strongly recommend engaging young surgeons in fellowship programs on structured laparoscopic colorectal surgery whenever possible before starting performing these procedures on their own.